Examining the effect of various vegetable oil-based cutting fluids on surface integrity in drilling steel - a review - Sultan, A.; Sharif, S.; Kurniawan, Denni (2014)
Increased attention on environmental and health impacts by industrial activities forces the manufacturing industry to reduce the mineral oil-based metalworking fluids as a cutting fluid. The advantages of using vegetable oil-based cutting fluids on tool wear and the cutting force have been reported in the literature, but those reporting the effects of their use on the surface finish of the workpiece are still lacking. This mini-review gives an overview of the influence of vegetable oilbased cutting fluids on surface integrity of steel during drilling process. Effect of the different cooling strategies on surface integrity is also presented. © (2014) Trans Tech Publications, Switzerland.